Exploration of Fiber-Reinforced Geopolymer Mortars Containing Recycled Aggregates and Marble Powder - Yilmaz, Arin; Erguen, Seckin; Uysal, Mucteba; Aygormez, Yurdakul; Aygun, Beyza Fahriye (SPRINGER HEIDELBERG, 2024)
Environmental and economic problems arising from cement production have made it necessary to find alternative binders. At this point, geopolymer mortars have come to the fore as an alternative construction material. In this study, 40% metakaolin + mineral additives (20% fly ash + 20% granulated blast furnace slag + 20% red mud) were used as binding material. NaOH (12M) and Na2SiO3 solutions were used. Recycling concrete aggregate and marble powder (MP) were used in equal proportions as aggregate. Different types of fibers (steel fiber (SF), polyamide fiber (PAF), and polypropylene fiber (PPF)) were used with different ratios (0.25, 0.50, 0.75, and 1%). In addition to mechanical properties (7, 28, and 56 days) such as compressive strength (CS), flexural strength (FS), and ultrasonic pulse velocity, high temperature, freezing-thawing, and sulfate resistances were performed. Results indicated that the series with 1% vol. SF had the highest unit weight and low water absorption, with the highest CS 38.5 MPa and FS 27.88% higher than the reference. However, considering the durability resistance, the best performance was observed in the series with 1% PPF by volume. The residual CS of this series after freezing-thawing was 32.95 MPa, the FS was 4.90 MPa, the CSs after Na2SO4 and Mg2SO4 were 38.32 MPa and 41.40 MPa, and FSs were 5.05 MPa and 4.41 MPa, respectively. Considering the abrasion resistance loss, the sequence of the series was as follows: 0.5% by volume PPF > 0.75% by volume PAF = 0.25% by volume SF.
Keywords: Alkali-activated materials; Mineral additives; Polypropylene fiber; Polyamide fiber; Steel fiber; Sustainability; FLY-ASH; RED MUD; MECHANICAL-PROPERTIES; SULFATE RESISTANCE; BUILDING MATERIAL; FREEZE-THAW; STRENGTH; CONCRETE; METAKAOLIN; WORKABILITY; Science & Technology - Other Topics